An Account of the First Aërial Voyage in England - Lunardi, Vincent (John Bell, 1784)
The book consists of a compilation of letters, newspaper reports, and illustrations detailing the first aerial voyage in England: Italian Vincenzo Lunardi's 24-mile flight in a hydrogen balloon from the Artillery Ground in London to Standon Green End on September 15, 1784.
Keywords: Balloonists; Balloon ascensions; Personal narratives--British; Ballooning; Lunardi, Vincent, 1759-1806